AN ASSESSMENT ON THE TREATY OF LAUSANNE IN ITS CENTURY ANNIVERSARY - Doğanay, Rahmi (Hamza ALTIN, 2023)
Like other states defeated in the First World War, the Ottoman Empire accepted the conditions imposed by the victorious Entente Powers, and had to accept first the Armistice of Mudros and then the Treaty of Sèvres. The Turkish nation, on the other hand, understood the true intention of the Entente Powers during the Armistice period, opposed the implementation of the Armistice and the occupations, and declared their demands on the Ottoman legacy with the Misakımilli text. During the National Struggle, he continued the struggle, ignoring the Treaty of Sèvres, which was imposed on the Ottoman Empire as a peace treaty. During the National Struggle, which it continued for 4 years to protect its existence and independence, it had to deal not only with the invaders, but also with the sultanate-caliphate opposition circles, especially the Istanbul governments. These circles, who did not see it as possible for the struggle against the victorious states to be successful, took sides with the invaders against the struggle in Anatolia. The fact that the National Struggle also covered the transition period from the sultanate to the republic, to a national and secular Turkey, was an important factor in this opposition. The military phase of the struggle for existence and non-existence under difficult conditions ended with the signing of the Mudanya Armistice. Immediately after, the TBMM Government, which abolished the sultanate on November 1, 1922, became the sole authority on the representation of the Turkish nation. At this stage, in the conference to be convened for peace negotiations, the TBMM Government sat at the table on equal terms with its interlocutors, not as the party that accepted the Armistice of Mudros and the Treaty of Sèvres, but as the winner of the years-long struggle for its law. The treaty was signed on 24 July 1923. The Treaty of Lausanne, as a victory won against those who imposed the Treaty of Sèvres, as well as the circles that accepted these conditions, not only made Turkey accept its rights to its interlocutors, but also defeated and liquidated the mentality that believed that there was no other way but to accept the terms of Sèvres. The victory of the National Struggle, which was the process of collision between Misakımilli and the Treaty of Sèvres, enabled the Treaty of Lausanne to be substituted for the Treaty of Sèvres. In our study, we will look at the Treaty of Lausanne a hundred years after its signing, and evaluate the claims and debates that have been brought to the agenda in the Republican period and in the present, to extent that amounts to speculation.

Birinci Dünya Savaşı’nda yenilen diğer devletler gibi, Osmanlı Devleti de galip İtilaf Devletlerinin dayattıkları şartları kabul etmiş, önce Mondros Mütarekesi’ni, daha sonra da Sevr Antlaşması’nı kabul etmek zorunda kalmıştı. Türk milleti ise İtilaf Devletlerinin gerçek niyetini daha Mütareke döneminde anlamış, Mütareke’nin uygulanmasına ve işgallere karşı çıkmış, Osmanlı mirası hakkındaki taleplerini, Misakımilli metni ile ilan etmiştir. Millî Mücadele sürecinde, Osmanlı Devleti’ne barış antlaşması olarak dayatılan Sevr Antlaşması’nı da yok sayarak mücadeleye devam etmiştir. Varlığını ve bağımsızlığını korumak için 4 yıl kadar sürdürdüğü Millî Mücadele sürecinde, sadece işgalcilere karşı değil, başta İstanbul hükümetleri olmak üzere içindeki saltanatçı-hilafetçi muhalifler çevrelerle de uğraşmak zorunda kalmıştır. Galip devletlere karşı mücadele etmenin başarı kazanmasını mümkün görmeyen bu çevreler, Anadolu’da verilen mücadeleye karşı işgalcilerin yanında saf da tutmuşlardı. Millî Mücadele’nin, saltanattan cumhuriyete, milli ve laik Türkiye’ye geçiş sürecini de kapsamış olması, bu muhalefette önemli bir etken olmuştu. Zor şartlar altında verilen varlık-yokluk mücadelesinin askeri safhası Mudanya Mütarekesi’nin imzalanmasıyla bitmişti. Hemen sonrasında, 1 Kasım 1922 tarihinde saltanatı kaldıran TBMM Hükümeti, Türk milletinin temsili konusunda tek yetkili duruma gelmiştir. Bu aşamada, barış görüşmeleri için toplanacak konferansta TBMM Hükümeti, Mondros Mütarekesi’ni ve Sevr Antlaşması’nı kabul eden taraf olarak değil, hukuku için verdiği yıllar süren mücadelenin galibi olarak, muhataplarıyla eşit şartlarda masaya oturmuştur. 24 Temmuz 1923 tarihinde antlaşma imzalanmıştır. Lozan Antlaşması, Türkiye’nin haklarını muhataplarına kabul ettirdiği gibi, Sevr Antlaşması’nı dayatanların yanında, Sevr şartlarını kabul etmekten başka yol olmadığına inanan zihniyeti de yenmiş ve tasfiye etmiştir. Misakımilli ile Sevr Antlaşması’nın çarpışması süreci olan Millî Mücadele’nin zaferle sonuçlanması, Sevr Antlaşması’nın yerine Lozan Antlaşması’nın ikame edilmesini sağlamıştır. Çalışmamızda, imzalanmasının Yüz yıl sonrasından Lozan Antlaşması’na bakacak, Cumhuriyet sürecinde ve güncelde, hakkında asılsız ve abartılı olarak gündeme getirilen iddialar ve tartışmalarla ilgili değerlendirmeler yapılacaktır.
YÜZÜNCÜ YILINDA LOZAN ANTLAŞMASI HAKKINDA BİR DEĞERLENDİRME
Keywords: History of The Republic of Turkiye; Türkiye Cumhuriyeti Tarihi